The effects of gender and marital status on burnout of English teachers in Iran - Asgari, Azadeh (Universiti Putra Malaysia Press, 2012)
Teacher burnout is a world-wide phenomenon that draws the attention of educational psychologists and stimulates efforts in construct elaboration and measurement. Emotional exhaustion, depersonalization, and lack of personal accomplishments are three dimensions that constitute the burnout syndrome. The purpose of this study was to determine the effects of gender and marital status on burnout of English teacher among 100 English teachers in Tehran, Iran. This paper describes the quantitative data obtained from the study. All the participants of the study were Iranian citizens who were working at secondary schools in Tehran. In order to determine the level of burnout experienced by English teachers, the Maslach Burnout Inventory test (MBI) was conducted. Based on the findings, the gender of English teacher seemed to have influenced the teacher’s responses on each of the sub-scales of the Maslach Burnout Inventory so there was a significant difference between the gender and burnout. The study also found that there was no significant difference between marital status and the English teacher’s score on the MBI.